Impact of the COVID-19 pandemic on patients with pre-existing mood disorders. (29th December 2022) - McLoughlin, James; O'Grady, Margaret M.; Hallahan, Brian
Abstract: Objectives: To examine the psychological and social impact of the COVID-19 pandemic on patients with established mood disorders during a period of stringent mandated social restrictions. Methods: Semi-structured interviews were conducted with 36 individuals attending the Galway–Roscommon Mental Health Services with an International Statistical Classification of Diseases and Related Health Problems, tenth revision (ICD-10) diagnosis of either Bipolar Affective Disorder (BPAD) ( n = 20) or Emotionally Unstable Personality Disorder (EUPD) ( n = 16) in this cross-sectional study. We determined the impact of the COVID-19 restrictions on anxiety and depressive symptoms, impulsivity, thoughts of self-harm, social and occupational functioning and quality of life. Results: The COVID-19 pandemic deleteriously impacted mental health (56.3% v. 15.0%, χ 2 = 7.42, p = 0.02), and mood (75.0% v. 20.0%, χ 2 = 11.17, p = 0.002) to a greater extent in the EUPD compared to the bipolar disorder cohort, with 43.8% of individuals with EUPD reporting an increase in suicidal ideation. Psychometric rating scales [Beck Anxiety Inventory (BAI), Beck Depression Scale (BDS), Beck Hopelessness Scale (BHS), Barratt Impulsivity Scale (BIS)] and Likert scales for anxiety, mood and quality of life noted significantly higher levels of psychopathology in the EUPD cohort ( p < 0.01). Qualitative analysis reflected quantitative data with themes of the employment of maladaptive coping mechanisms and reduced mental health supports notable. Conclusions: Individuals with EUPD are experiencing significant mental health difficulties related to the COVID-19 pandemic. The provision and recommencement of therapeutic interventions to this cohort, in particular, are warranted given the significant distress and symptoms being experienced.